2011
DOI: 10.5586/asbp.2003.033
|View full text |Cite
|
Sign up to set email alerts
|

RAPD markers and black pine (Pinus nigra Arnold) intraspecies taxonomy - Evidence from the study of nine populations

Abstract: Although intraspecies researches within the black pine (Pinus nigra Arnold) have a long tradition, the intraspecies taxonomy, classification and chorology are still unclear. Among the numerous reasons that have caused this situation the most important are: the absence of a study that would completely cover the whole range of this species, the impossibility of connection of results of the existing detailed studies of certain areas, and the high variability of traits which have been used so far. Since the charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 15 publications
(18 reference statements)
1
13
0
1
Order By: Relevance
“…It is interesting that Liber et al . , using the random amplified polymorphic DNA (RAPD), also pointed to the existence of several P. nigr a groups on the territory of western Balkans (subsp. illyrica , subsp.…”
Section: Resultsmentioning
confidence: 98%
“…It is interesting that Liber et al . , using the random amplified polymorphic DNA (RAPD), also pointed to the existence of several P. nigr a groups on the territory of western Balkans (subsp. illyrica , subsp.…”
Section: Resultsmentioning
confidence: 98%
“…Biochemical and molecular markers recognise the P. nigra subspecies, but with low taxonomical resolution (Nikolić & Tucić 1983; Aguinagalde et al. 1997; Liber et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical and molecular markers recognise the P. nigra subspecies, but with low taxonomical resolution (Nikolić & Tucić 1983;Aguinagalde et al 1997;Liber et al 2003). The recent cpSSR study of Raffi & Dodd (2007) showed high within-and low among-population differences across the western range of European black pine, differentiating it into six geographic regions of molecular variation.…”
Section: Introductionmentioning
confidence: 99%
“…) is the southernmost subspecies of black pine, and is endemic along the Western Moroccan Rif and the Algerian Tell Atlas (Liber et al, 2003;Qu ezel & M edail, 2003). mauretanica (Maire et Peyerimh.…”
Section: Introductionmentioning
confidence: 99%
“…mauretanica (Maire et Peyerimh. ) is the southernmost subspecies of black pine, and is endemic along the Western Moroccan Rif and the Algerian Tell Atlas (Liber et al, 2003;Qu ezel & M edail, 2003). Currently, an extremely limited number of plants still persist within the natural range (M edail & Diadema, 2009), giving this taxon an outstanding ecological importance (Arbez & Millier, 1971;Seigue, 1985).…”
Section: Introductionmentioning
confidence: 99%